G6PD activity in whole blood distinguishes the pattern of vascular complications in type 2 diabetes - Farah Kourdi; Mahassen Al-qubaji; Mohamad Sami Joha (Zagazig Journal of Pharmaceutical Sciences)
BACKGROUND: Hyperglycemia in type 2 of diabetes significantly contributes to oxidative load, which in turn promotes the evolution of vascular complications. Since Glucose-6-phosphate dehydrogenase (G6PD) is a key enzyme in antioxidant defense, our study aimed to evaluate the correlation between G6PD activity and the presence and pattern of vascular complications in individuals with type 2 diabetes. MATERIALS AND METHODS: The total blood G6PD activity and fasting blood glucose (FBG) levels were compared between two groups of patients and a group of 44 healthy individuals. The first group of patients included 80 type 2 diabetic patients without vascular complications, while the second group comprised 44 type 2 diabetic patients with macrovascular complications and 36 type 2 diabetic patients with microvascular complications. HbA1c and creatinine values were too compared between the two patient groups. FBG and creatinine levels were measured using colorimetric methods, HbA1c was assessed by a fluorescence immunoassay, and total blood G6PD was determined using a kinetic method assay. Statistical tests were conducted using IBM SPSS Statistics 26. RESULTS: The study revealed a rise in G6PD activity among patients with macrovascular complications, while its activity decreased in patients with microvascular complications. Additionally, G6PD activity exhibited a negative correlation with creatinine levels in patients with microvascular complications. CONCLUSIONS: This study suggests that measuring G6PD activity in whole blood could serve as a differential and prognostic marker for vascular complications. This study also demonstrates, for the first time, that high creatinine levels may indicate low antioxidant activity in type 2 diabetic patients.